Developing a measure of educator self-efficacy around emotion co-regulation - Lindstrom Johnson, Sarah; Meléndez Guevara, Ana Maria; Preves, Ashley (Frontiers in Education, 2023)
Research suggests that one of the most pervasive consequences of traumatic events is the resulting dysregulation of emotions. Educators, including teachers, administrators, and student services staff, are instrumental in supporting students as they navigate overwhelming emotions by modeling and teaching skills to regulate emotional states (i.e., emotion co-regulation). Given the saliency of emotion co-regulation within educational context, this study presents the development and preliminary psychometric exploration of a measure of educator self-efficacy for co-regulation. We examined differences by educator characteristics (gender, professional experience, role in the school) as well as previous training in trauma-informed approaches and culturally responsive strategies. Preliminary findings support the measure to be reliable and valid, with construct validity supported by positive associations to other theoretically applicable constructs such as culturally responsive strategies, as well as educator characteristics such as professional experience and role. However, a lack of association with trauma-informed training, suggests the need for additional research into supporting emotion co-regulation self-efficacy for educators.